(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article is devoted to the stylistic means of lexical-semantic information texts. Considers the functioning of the semantic content of those tropes as antonomasia, dysphemism.